Effect of HIV and Interpersonal Trauma on Cortical Thickness, Cognition, and Daily Functioning. (1st August 2020) - Kapetanovic, Suad; Norato, Gina; Nair, Govind; Julnes, Peter Siyahhan; Traino, Katherine A.; Geannopoulos, Katrina; Smith, Bryan R.; Snow, Joseph; Nath, Avindra
Abstract : Background: Interpersonal trauma (IPT) is highly prevalent among HIV-positive (HIV+) individuals, but its relationship with brain morphology and function is poorly understood. Setting: This cross-sectional analysis evaluated the associations of IPT with cognitive task performance, daily functioning, magnetic resonance imaging (MRI) brain cortical thickness, and bilateral volumes of 4 selected basal ganglia regions in a US-based cohort of aviremic HIV+ individuals, with (HIV+ IPT+) and without IPT exposure (HIV+ IPT−), and sociodemographically matched HIV-negative controls with (HIV− IPT+) and without IPT exposure (HIV− IPT−). Methods: Enrollees completed brain MRI scans, a semistructured psychiatric interview, a neurocognitive battery, and 3 measures of daily functioning. Demographic and clinical characteristics of the 4 groups were described, and pairwise between-group comparisons performed using χ 2 tests, analysis of variance, or t -tests. Linear or Poisson regressions evaluated relationships between group status and the outcomes of interest, in 6 pairwise comparisons, using Bonferroni correction for statistical significance. Results: Among 187 participants (mean age 50.0 years, 63% male, 64% non-white), 102 were HIV+ IPT+, 35 were HIV+ IPT−, 26 were HIV− IPT−, and 24 were HIV− IPT+. Compared with the remaining 3 groups, the HIV+ IPT+ group had more activities of daily living declines, higher number of impaired Patient's Assessment of Own Functioning Inventory scores, and lower cortical thickness in multiple cerebral regions. Attention/working memory test performances were significantly better in HIV− IPT− compared with the HIV+ IPT+ and HIV+ IPT− groups. Basal ganglia MRI volumes were not significantly different in any between-group comparisons. Conclusion: IPT exposure and HIV infection have a synergistic effect on daily functioning and cortical thickness in aviremic HIV+ individuals. Abstract : Supplemental Digital Content is Available in the Text.